Harlequin Syndrome in a Case of Toxic Goitre: A Rare Association - P. V. Pradeep (Case Reports in Medicine, 2011)
Harlequin syndrome (HS) is known to be associated with conditions like brain stem infarcts and superior mediastinal neurinoma. However, it has not been reported in association with autoimmune hyperthyroidism. We report a case of exacerbation of unilateral sweating in a patient with HS following the onset of toxic goitre. Previous reports have suggested that a tortuous inferior thyroid artery can produce neurovascular compression of the sympathetic chain which was not observed in our patient. Autoimmune aetiology for HS needs to be explored. Increased sweating in hyperthyroid patients needs to be assessed properly so as to prognosticate appropriately.